A new application-layer overlay platform for better connected vehicles - Jaemin Jang; Taemin Ahn; Junghee Han (International Journal of Distributed Sensor Networks)
To support smart and converged services for autonomous vehicles, reliable vehicular ad hoc networks play important roles. To achieve this goal, this article proposes an application-layer overlay platform for hyper-connected vehicular ad hoc networks. By effectively exploiting redundancy of communication among vehicles and infrastructures on the road, this article aims to provide reliable communications among vehicles with high performance. Furthermore, the proposed approach is built at the application layer, and hence, it is compatible with existing routing protocols. Also, it minimizes communication and computation overheads. To verify the proposed scheme, we evaluate performance of the proposed approach compared with existing routing protocols.